NSG Mice Facilitate ex vivo Characterization of Ewing Sarcoma Lung Metastasis Using the PuMA Model - Scopim-Ribeiro, Renata; Lizardo, Michael M.; Zhang, Hai-Feng; Dhez, Anne-Chloé; Hughes, Chistopher S.; Sorensen, Poul H. (Frontiers in Oncology, 2021)
Ewing sarcoma (EwS) is a highly malignant bone and soft tissue tumour primarily affecting children and young adults. While most patients initially respond well to conventional front-line therapy, frequent metastasis results in poor 5-year overall survival rates for this disease. Accordingly, there is a critical need to develop better models to understand EwS metastasis. We and others previously used the ex vivo pulmonary metastasis assay (PuMA) to study lung metastasis in solid tumours including osteosarcoma (OS), but this technique has to date not been achievable for EwS. PuMA involves tail vein injection of fluorescent tumour cells into NOD-SCID mice, followed by their visualization in long-term cultures of tumour-bearing lung explants. Here we demonstrate successful implementation of PuMA for EwS cells using NOD-SCID-IL2 receptor gamma null (NSG) immunocompromised mice, which demonstrated high engraftment of EwS cell lines compared to NOD-SCID mice. This may be linked to immune permissiveness required by EwS cells, as increased basal cytotoxicity of EwS cells was observed in NOD-SCID compared to NSG lung sections, possibly due to the absence of natural killer (NK) cell activity in the latter. Together, our data demonstrate the utility of NSG mice for PuMA modeling of EwS lung metastasis.